Institutions and mechanisms for internal conflict resolutions in Malaysia - Mokhtar, Khairil Azmin (2011)
The paper deals with major dispute resolution mechanisms and institutions which are available in order to deal with conflicts within a country. Although the discussion is generally made within the Malaysian constitutional context, the paper also touches on the mechanisms and institutions in other countries where relevant. It shall highlight the advantages and disadvantages of the various means for resolving conflict. The paper also seeks to highlight certain constitutional aspects or issues which are regarded as relevant and important in order to accommodate the implementation of solutions achieved through social, political and other non-legal means. The paper also touches on the prospects of certain institutions and mechanisms, and probable future challenges. Among the institutions and mechanism that will be studied are the judiciary and judicial review, the legislature and constitutional amendment, human rights commission, mediation and conciliation, and the traditional and religious institutions.